Korelasi Nilai-nilai Tasawuf dengan Permasalahan Mental di Era Modern - Diana Putri (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the correlation of Sufism values with mental problems in the modern era. This study uses a qualitative approach by applying a descriptive-analytical method. The results of this study indicate that there is a correlation between Sufism values and mental problems in the modern era. This study concludes that the concepts of Sufism and psychology have a common point of contact or thread, namely the meaning of mental health and the same goal of Sufism and psychology, namely to gain prosperity and peace in life. Therefore, the teachings of Sufism are one of the solutions that can be used to deal with mental problems in this modern era.